ANALISA DAN PERANCANGAN SISTEM KEY PERFORMANCE INDICATOR BERBASIS WEB - Santika, Nisa; Iqbal, Mohammad; Apandi, Tri Herdiawan (UPPM Polsub, 2019)
Key Performance Indicator is one of the performance assessment systems commonly used by companies. PT. SIL is one company that uses the KPI system for its employees. The use of a system that is still problematic in adjusting employee data with performance values and the selection of the wrong type of category results in the use of the system not running optimally. Knowing this is the management of data indicators and calling employee data automatically becomes a solution. In addition, restrictions on access rights based on each user become easier to understand.Keywords: KPI, Indicator, Performance Assessment.